The Combined Inoculation of Curvularia lunata AR11 and Biochar Stimulates Synthetic Silicon and Potassium Phosphate Use Efficiency, and Mitigates Salt and Drought Stresses in Rice - Adhikari, Arjun; Khan, Muhammad Aaqil; Imran, Muhammad; Lee, Ko-Eun; Kang, Sang-Mo; Shin, Jin Y.; Joo, Gil-Jae; Khan, Murtaza; Yun, Byung-Wook; Lee, In-Jung (Frontiers in Plant Science, 2022)
Synthetic chemical fertilizers are a fundamental source of nutrition for agricultural crops, however, their limited availability, low plant uptake, and excessive application have caused severe ecological imbalances. In addition, the gravity of environmental stresses, such as salinity and water stress, has already exceeded the threshold limit. Therefore, the optimization of nutrient efficiency in terms of plant uptake is crucial for sustainable agriculture production. To address these challenges, we isolated the rhizospheric fungus Curvularia lunata ARJ2020 (AR11) and screened the optimum doses of biochar, Si, and K2HPO4, and used them—individually or jointly—to treat rice plants subjected to salt and low water stress. Bioassay analysis revealed that AR11 is a highly halotolerant and drought-resistant strain with an innate ability to produce gibberellin (GA1, GA3, GA4, and GA7) and organic acids (i.e., acetic, succinic, tartaric, and malic acids). In the plant experiment, the co-application of AR11 + Biochar + Si + K2HPO4 significantly improved rice growth under both salt and drought stresses. The stress hormone, known as abscisic acid, was significantly reduced in co-application-treated rice plants exposed to both drought and salt stress conditions. These plants showed higher Si, P, and K contents and a markedly low Na+ ion concentration. The results were further validated by the higher expression of the Si-carrying gene OsLSi1, the salt-tolerant gene OsHKT2, and the OsGRAS23’s drought-tolerant transcriptome. Interestingly, the beneficial effect of AR11 was significantly higher than that of the co-application of Biochar+Si+K2HPO4 under drought. Moreover, the proline content of AR11-treated plants decreased significantly, and an enhancement of plant growth-promoting characteristics was observed. These results suggest that the integrated co-application of biochar, chemical fertilizers, and microbiome could mitigate abiotic stresses, stimulate the bioavailability of essential nutrients, relieve phytotoxicity and ultimately enhance plant growth.